The Effects of Low and High Levels of Sadness on Scope of Attention: An ERP Study - Wang, Hailu; Chen, Ying; Zhang, Qin (Frontiers in Psychology, 2018)
Sadness has inconsistent effects on the scope of attention. These differing effects may be attributed to different levels of sadness induced in different experiments. Low levels of sadness can expand the scope of attention, but high levels can narrow it. In this study, we recruited 42 college students and induced different levels of sadness in them by having them view sad images continuously, and then we assigned them Navon’s letter task. The results showed that among participants with local-processing bias, those at lower levels of sadness were slower to identify small letters than were those at high levels of sadness and control condition (watching neutral images). Event-related potential (ERP) results showed that low-sadness participants put more attention resources toward processing large letters (global stimuli). They showed increased amplitude of the P1 component compared with high-sadness participants and participants at control condition. These results suggested that different levels of sadness had different effects on attention scope: low levels of sadness extended the scope but as sadness increased, this extension disappeared. This influence pattern mainly occurred in the early stages of visual processing.